Pola pengasuhan yang relevan untuk pengembangan karakter anak pada era teknologi digital dan globalisasi - Samho, Bartolomeus (Academy of Education Journal, 2024)
Children's lives today are marked by the sophistication of digital technology which has culminated in globalization. On the one hand, digital technology helps us in many ways, but on the other hand, it also poses problems for the development of children's character because they may not be able to use it properly as well as their parents hope. Therefore, without denying the positive benefits of digital technology for the dissemination of information and communication, it can also cause problems for the development of children's character, in particular, related to parenting patterns in the family and the internalization of values to strengthen their positive character. This article aims to describe parenting patterns in families in the era of digital technology which the author views as relevant for developing children's character. The writing method used in this research is qualitative. The results of this research show that the relevant parenting patterns in the era of digital technology are those based on the example of parents. Therefore, the main problem raised in this article is what are the threats and challenges of digital technology for children's character development? What parenting patterns in the era of digital technology are considered relevant for children's character development?